2021
DOI: 10.1021/acs.energyfuels.1c01357
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Insight into the Behavior of Ions at an Oil-Bearing Hydrated Calcite Surface: Implication to Ion-Engineered Waterflooding

Abstract: This research provides an atomistic picture of the role of ions in modulating the microstructural features of an oil-contaminated calcite surface. This is of crucial importance for the rational design of ion-engineered waterflooding, a promising technique for enhancing oil recovery from carbonate reservoirs. Inspired by a conventional lab-scale procedure, an integrated series of molecular dynamics (MD) simulations were carried out to resolve the relative contribution of the major ionic constituent of natural b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 74 publications
(142 reference statements)
3
9
0
Order By: Relevance
“…Besides, salinity would influence the surfactant-calcite carbonate interaction force. The heavy oil-calcium carbonate interfacial behavior was influenced by the CaCO 3 mineral surface chemistry and polar hydrocarbons residing charged ( Badizad et al, 2021 ). The surfactant adsorption onto the calcite surface was also influenced by the CaCO 3 mineral surface chemistry and polar hydrocarbons residing charge.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, salinity would influence the surfactant-calcite carbonate interaction force. The heavy oil-calcium carbonate interfacial behavior was influenced by the CaCO 3 mineral surface chemistry and polar hydrocarbons residing charged ( Badizad et al, 2021 ). The surfactant adsorption onto the calcite surface was also influenced by the CaCO 3 mineral surface chemistry and polar hydrocarbons residing charge.…”
Section: Resultsmentioning
confidence: 99%
“…The decane, BA molecules, Na + , and Cl – ions were modeled using the OPLS-AA force field . Recent studies have shown the compatibility of these force fields to reproduce the correct physical system. , The EPM2 model was utilized to describe the carbon dioxide molecules.…”
Section: Methodsmentioning
confidence: 99%
“…Particularly, in the case of calcium carbonate reservoirs, a key mechanism is the preferential adsorption of specific ions on the carbonate surface, i.e., MIE. 33,34 Moreover, some studies have indicated that the presence of divalent ions in seawater, such as sulphate anions (SO 4 2À ), and calcium (Ca 2+ ) and magnesium (Mg 2+ ) cations, can displace monovalent ions (mainly Na + cations) adsorbed on the carbonate surface, which increases wettability to water, improves crude oil release and facilitates good production. 34 Recently, the effectiveness of the SW in the EOR has been demonstrated in both laboratory and field studies.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Moreover, some studies have indicated that the presence of divalent ions in seawater, such as sulphate anions (SO 4 2À ), and calcium (Ca 2+ ) and magnesium (Mg 2+ ) cations, can displace monovalent ions (mainly Na + cations) adsorbed on the carbonate surface, which increases wettability to water, improves crude oil release and facilitates good production. 34 Recently, the effectiveness of the SW in the EOR has been demonstrated in both laboratory and field studies. 30,[35][36][37][38] For example, Zallaghi et al studied the synergy that occurs when SW and surfactants are injected into carbonate reservoirs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation